2021
DOI: 10.1002/dmrr.3451
|View full text |Cite
|
Sign up to set email alerts
|

Serum‐ and glucocorticoid‐inducible kinase 1 promotes insulin resistance in adipocytes via degradation of insulin receptor substrate 1

Abstract: Aims Accumulating evidence indicates that serum‐ and glucocorticoid‐inducible kinase 1 (SGK1) plays a role in the development of metabolic syndrome via a poorly understood mechanism. This study aimed to investigate the direct effect of SGK1 on insulin sensitivity in adipose tissue. Materials and methods We ectopically expressed or silenced SGK1 in adipocytes via lentiviral transfection, measured glucose uptake and evaluated insulin signalling using western blotting. In vivo insulin resistance was measured at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
0
14
1
Order By: Relevance
“…Inhibition of SGK1 expression by short hairpin RNA lentivirus led to reduced expression of adipogenic differentiation genes and increased expression of cell proliferation genes. The inhibition of insulin signalling by dexamethasone and oleic acid was reversed by lv-shSGK1 [41], whereas we observed that loss-of-function SGK1 led to down-regulation of proteins related to differentiation (PPARγ and C/EBPα) and no changes in proteins related to proliferation (CCDN2 and CDK2). This suggests that sh-SGK1 repressed bovine adipogenesis mainly by inhibiting adipocytes differentiation.…”
Section: Discussioncontrasting
confidence: 59%
“…Inhibition of SGK1 expression by short hairpin RNA lentivirus led to reduced expression of adipogenic differentiation genes and increased expression of cell proliferation genes. The inhibition of insulin signalling by dexamethasone and oleic acid was reversed by lv-shSGK1 [41], whereas we observed that loss-of-function SGK1 led to down-regulation of proteins related to differentiation (PPARγ and C/EBPα) and no changes in proteins related to proliferation (CCDN2 and CDK2). This suggests that sh-SGK1 repressed bovine adipogenesis mainly by inhibiting adipocytes differentiation.…”
Section: Discussioncontrasting
confidence: 59%
“…The current knowledge was compiled in a gene regulation network of TH9 cells, which overlaps with T H 2 and T H 17 networks. The references for the network are as follows: [a:(Zhou et al, 2013), b:(Goswami et al, 2012), c:(Popp et al, 2017), d:(Chang et al, 2010), e:(Yee et al, 1998), f:(Mullen et al, 2011), g:(Mudter et al, 2011), h 50 , i:(Malik et al, 2017), j:(Takami et al, 2012), k:(Jash et al, 2012), l:(Kleinewietfeld et al, 2013), m:(Lu et al, 2010), n:(Seoane et al, 2004), o:(Harada et al, 2010), p:(Wu et al, 2020), q:(Takimoto et al, 2010), r:(Lee et al, 2019), (Jabeen et al, 2013), s:(Sahu et al, 2017), (Zhou et al, 2013)]. (B) CD4 + T cells were isolated from digested lungs of non-allergic and allergic WT and iCD4TGFBR2 mice and analyzed for IL-9 expression as well as T H 9 and T H 2 relevant transcription factors and signal molecules using quantitative RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…S2773; Selleck Chemicals). To overexpress SGK1 in MBSMCs, according to the literature, 25 , 26 the concentrations of Dex were 0, 1, 5, 10, 15 and 20 μmol/L, and culture medium containing 10% FBS was used. After 6 and 12 h, total cellular protein or supernatant was collected.…”
Section: Methodsmentioning
confidence: 99%